COVID-19 experiences and cruise booking behavior: Insights from YouTube viewers applying revised protection motivation theory - Park, Sung-Su; Song, Won-Ick; Ahn, Byoung-Wook (Journal of Asian Scientific Research, 2024)
The purpose of this study is to examine the relationship between risk perceptions (crowding risk perception, health risk perception) and self-protective behavioral intentions and booking intention for COVID-19 using the theory of protection motivation previously verified in the study and to analyze the structural relationship between all variables. In particular, it was intended to investigate the specific impact relationship between COVID-19 risk perception, including crowding risk perception and health risk perception, and self-protective behavior and cruise booking intention. The survey was conducted on subscribers of travel YouTube channels with cruise video content, and the respondents actively responded by providing convenience store beverage coupons. In an online survey conducted for a month from January 15, 2023, 312 samples were collected from travelers who have experienced cruises in the past five years. SPSS and AMOS statistical programs were used, and first, frequency analysis and discriminant validity analysis were verified. In addition, the verification of structural relevance between variables was analyzed by the covariance-based structural equation modeling (CB-SEM). Demographic characteristics, confirmatory factor analysis, correlation analysis, and structural model analysis verified the hypothesis. Based on the results of the analysis, this study presents basic evidence useful for establishing management strategies for cruise companies.